2015
DOI: 10.1111/1750-3841.12761
|View full text |Cite
|
Sign up to set email alerts
|

Surface Properties of Heat‐Induced Soluble Soy Protein Aggregates of Different Molecular Masses

Abstract: Suspensions (2% and 5%, w/v) of soy protein isolate (SPI) were heated at 80, 90, or 100 °C for different time periods to produce soluble aggregates of different molecular sizes to investigate the relationship between particle size and surface properties (emulsions and foams). Soluble aggregates generated in these model systems were characterized by gel permeation chromatography and sodium dodecyl sulfate-polyacrylamide gel electrophoresis. Heat treatment increased surface hydrophobicity, induced SPI aggregatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 102 publications
(48 citation statements)
references
References 45 publications
0
46
0
Order By: Relevance
“…In the absence of rutin, SW‐induced protein (HSPI) has a significantly ( P < 0.05) larger hydrodynamic radius ( R h ) than native protein (NSPI), but R h did not differ significantly before and after the introduction of rutin for native and heated protein, which agrees well with the previous observations on the enrichment of catechin to pectin (Oliveira and others ). This phenomenon was attributed to the unfolded proteinsand soluble aggregates formation during SW treatment (Wang and others ; Guo and others ). The hydrodynamic radius of NSPI–rutin mixture was smaller than that for NSPI, as well as for the HSPI–rutin mixture compared to HSPI.…”
Section: Resultsmentioning
confidence: 97%
“…In the absence of rutin, SW‐induced protein (HSPI) has a significantly ( P < 0.05) larger hydrodynamic radius ( R h ) than native protein (NSPI), but R h did not differ significantly before and after the introduction of rutin for native and heated protein, which agrees well with the previous observations on the enrichment of catechin to pectin (Oliveira and others ). This phenomenon was attributed to the unfolded proteinsand soluble aggregates formation during SW treatment (Wang and others ; Guo and others ). The hydrodynamic radius of NSPI–rutin mixture was smaller than that for NSPI, as well as for the HSPI–rutin mixture compared to HSPI.…”
Section: Resultsmentioning
confidence: 97%
“…With an appropriate temperature-time combination, for example, 80°C for 30 min or 90°C for a few seconds, soy and whey proteins can undergo certain conformational change to expose hydrophobic groups (Feng, Xiong, & Mikel, 2003). Aggregates formed by subsequent hydrophobic and disulfide aggregation also contribute to the emulsifying activity and emulsion stability (Guo et al, 2015;. Knudsen, Øgendal, and Skibsted (2008) found that thermal aggregates of β-lactoglobulin, the most abundant protein in whey, improved the apparent viscosity of emulsions.…”
Section: Heatingmentioning
confidence: 99%
“…Generally, after thermal denaturation, unfolding, and molecular aggregation, soybean proteins were cross-linked to form a three-dimensional network gel [2]. It has been reported that many factors can affect the formation of protein gels, such as pH, coagulant, heating method, protein concentration, and addition of sugars [3][4][5]. Therefore, it is valuable to study the effects of other ingredients and treatment conditions on the production of protein-based products.…”
Section: Introductionmentioning
confidence: 99%